Control System Automatic for Light And Air Conditioner at Living Room using Arduino Uno Controller - Hamam Nasirrudin; Budi Prijo Sembodo (BEST, 2022)
In Indonesia, the usage of electrical energy is still poorly handled. Few people realize how important it is to conserve electricity. Electricity waste, such as the usage of air conditoner (AC) and lighting, is more common in public buildings. Few People realize how important it is to conserve electricity. Electricity waste, such as the usage of air conditioners (AC) and lighting, is more common in public buildings. The goal of this study is to find a way to reduce electricity waste. The HCSR04 Ultrasonic sensor is used to detect things in this system, and the signal from the sensor is received by Arduino Uno and processed into data. Following the processing of the data, the Arduino Uno instructs the AC and lights to turn on, as well as the LCD to display the identified items. This system is put on a table near the room’s door for use. The system as a whole can function well after testing.